Treatment-related improvement in neuropsychological functioning in suicidal depressed patients: Paroxetine vs. bupropion. Issue 3 (28th February 2015) - Gorlyn, Marianne; Keilp, John; Burke, Ainsley; Oquendo, Maria; Mann, J. John; Grunebaum, Michael
Abstract: Neuropsychological dysfunction is associated with risk for suicidal behavior, but it is unknown if antidepressant medication treatment is effective in reducing this dysfunction, or if specific medications might be more beneficial. A comprehensive neuropsychological battery was administered at baseline and after 8 weeks of treatment within a randomized, double-blind clinical trial comparing paroxetine and bupropion in patients with DSM-IV Major Depressive Disorder and either past suicide attempt or current suicidal thoughts. Change in neurocognitive performance was compared between assessments and between medication groups. Treatment effects on the Hamilton Depression Rating Scale and Scale for Suicide Ideation were compared with neurocognitive improvement. Neurocognitive functioning improved after treatment in all patients, without clear advantage for either medication. Improvement in memory performance was associated with a reduction in suicidal ideation independent of the improvement of depression severity. Overall, antidepressant medication improved neurocognitive performance in patients with major depression and suicide risk. Reduced suicidal ideation was best predicted by a combination of the independent improvements in both depression symptomatology and verbal memory. Targeted treatment of neurocognitive dysfunction in these patients may augment standard medication treatment for reducing suicidal behavior risk. Highlights: A comprehensive neuropsychological battery was administered to depressed patients at elevated risk for suicide before and after treatment in a clinical trial. Patients were treated with paroxetine or bupropion for 8 weeks. Neurocognitive functioning improved after treatment in all patients, without clear advantage for either medication. Improvement in memory performance was associated with reduced suicidal ideation independent of the improvement of depression severity. Targeted treatment of neurocognitive dysfunction may bring about greater reduction in risk for reducing suicidal behavior.